2009
DOI: 10.1021/jp9034453
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Chemiresistor Sensors in Aqueous Solution: Comparison of Hydrophobic and Hydrophilic Nanoparticle Films

Abstract: Chemiresistor sensors based on thin films of gold nanoparticles capped with hydrophobic hexanethiol or hydrophilic 6-hydroxyhexanethiol self-assembled monolayers are shown to respond to organic analytes in aqueous solution. Although considerable swelling of the 6-hydroxyhexanethiol-capped nanoparticle film by water occurred, the 6-hydroxyhexanethiol-capped nanoparticle film still responded toward the presence of organic analytes in aqueous solution. The response toward nonpolar analytes (toluene, hexane, dichl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
0
44
0
1
Order By: Relevance
“…2 and 3). It has previously been shown that the resistance of Au NP films increase proportionally to the concentration of analytes that partition into the nanoparticle film [29]. Based on this, the data suggests that as E. coli grow, the sensors detect an initial decrease in analyte(s) concentration followed by an increase.…”
Section: Discussionmentioning
confidence: 89%
“…2 and 3). It has previously been shown that the resistance of Au NP films increase proportionally to the concentration of analytes that partition into the nanoparticle film [29]. Based on this, the data suggests that as E. coli grow, the sensors detect an initial decrease in analyte(s) concentration followed by an increase.…”
Section: Discussionmentioning
confidence: 89%
“…The chemiresistors function by a change in electrical resistance of the gold nanoparticle films by the partitioning of analytes into the organic caps surrounding the nanoparticles [12,13]. However, it has also been shown that the response towards analytes can depend on the nanostructure of the functionalised nanoparticle film and the method of film formation [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of chemical sensing, we are interested in determining the porosity of gold nanoparticle films that are used as chemiresistive materials in liquids [11,13,[30][31][32][33][34][35][36]. The assembly of multilayered gold nanoparticles produces a disordered porous film [37].…”
mentioning
confidence: 99%
“…The distinct features of nanostructured 2D Au arrays can be summarized by outlining recent achievements. First, Au thin films fabricated by alkylthiol-functionalized Au NPs were found to have vapor sensitive conductivities [7,8], they were hence widely investigated as electrical chemiresistors for sensing different vapor analytes [9][10][11] and even organic molecules in aqueous solutions [12,13]. Second, Au thin films were demonstrated to have special localized surface plasmon resonances (LSPR) [14][15][16], so that highly ordered 2D Au superlattices showed strong collective LSPR bands due to the near-field coupling of adjacent nanoparticles [17] and were employed to detect biomolecular binding [18].…”
Section: Introductionmentioning
confidence: 99%